2020
DOI: 10.3847/1538-4357/abb594
|View full text |Cite
|
Sign up to set email alerts
|

Shear-driven Transition to Isotropically Turbulent Solar Wind Outside the Alfvén Critical Zone

Abstract: Motivated by prior remote observations of a transition from striated solar coronal structures to more isotropic “flocculated” fluctuations, we propose that the dynamics of the inner solar wind just outside the Alfvén critical zone, and in the vicinity of the first surface, is powered by the relative velocities of adjacent coronal magnetic flux tubes. We suggest that large-amplitude flow contrasts are magnetically constrained a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 75 publications
3
123
2
Order By: Relevance
“…It has been proposed that switchbacks may form as the solar wind evolves, being produced by turbulence or velocity shears (Ruffolo et al 2020;Squire et al 2020). This is supported by the studies of Mozer et al (2020) and Macneil et al (2020) who found that the occurrence of switchbacks increases with radial distance from the Sun r. While we cannot conclude on switchback occurrence at radial distances greater than 60 R s , our analysis suggests that it is unrelated to heliocentric radial distance near the Sun (see Sections 3.1 and 4).…”
Section: Turbulent Generation Of Switchbackssupporting
confidence: 82%
“…It has been proposed that switchbacks may form as the solar wind evolves, being produced by turbulence or velocity shears (Ruffolo et al 2020;Squire et al 2020). This is supported by the studies of Mozer et al (2020) and Macneil et al (2020) who found that the occurrence of switchbacks increases with radial distance from the Sun r. While we cannot conclude on switchback occurrence at radial distances greater than 60 R s , our analysis suggests that it is unrelated to heliocentric radial distance near the Sun (see Sections 3.1 and 4).…”
Section: Turbulent Generation Of Switchbackssupporting
confidence: 82%
“…This mechanism was first proposed by Landi et al (2005Landi et al ( , 2006. A slightly different version, involving the nonlinear instability of such sheared flows, has been proposed by Ruffolo et al (2020). This mechanism mainly leads to a slow-mode (pressure-balanced) contribution to the switchback.…”
Section: Discussionmentioning
confidence: 98%
“…Observational studies invoke the formation of these structures either by processes occurring deep in the solar atmosphere (Dudok de Wit et al 2020;Krasnoselskikh et al 2020;Macneil et al 2020;Woodham et al 2021) or directly in the solar wind (Ruffolo et al 2020). These two types of origins have also been explored on the numerical and theoretical side: on the one hand, via interchange reconnection in the corona (Fisk & Kasper 2020;Drake et al 2021) or jets in the solar atmosphere (Roberts et al 2018;Sterling & Moore 2020;He et al 2020); on the other hand, via waves growth generated by the expansion of the structure away from the Sun (Squire et al 2020) or shear-driven turbulence in the solar wind (Ruffolo et al 2020). As of today, the mechanisms leading to the formation of switchbacks is still unclear and it is unknown whether different populations of switchbacks might be generated by distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%